The Missing Link: Knowledge Management and the Social Dimension of Business-IT Alignment - Kloth, Rikard; Jonathan, Gideon Mekonnen (Complex systems informatics and modeling quarterly, 2025)
Business-IT alignment (BITA) remains a persistent challenge for organizations seeking to derive strategic value from their IT investments. While substantial research has explored the strategic and intellectual dimensions of the construct, the social dimension, centered on communication, shared understanding, and collaboration between business and IT leaders, has received relatively limited attention. At the same time, knowledge management (KM) has emerged as a vital organizational capability, particularly in the context of digital transformation and evolving Environmental, Social, and Governance (ESG) imperatives. However, the intersection of KM and the social dimension of BITA remains underexplored, especially in large enterprise settings. To address this gap in the literature, this study investigates how KM practices contribute to enhancing the social dimension of BITA within a large Swedish company undergoing digital transformation. Drawing on Nonaka’s SECI model as a conceptual lens and employing a qualitative case study methodology (based on nine semi-structured interviews and internal document analysis), the study identified key impediments to social alignment, including reliance on outsourced IT, knowledge erosion due to staff turnover, fragmented communication, and siloed planning. The results also reveal how KM practices – including in-house development, knowledge-sharing forums, agile methods, and transparent digital communication tools – facilitate knowledge exchange, socialization, and shared domain understanding. The study contributes to the literature by advancing the conceptual integration of KM and BITA, offering empirical insights into the role of KM practices in fostering social alignment, and proposing refinements to existing BITA frameworks by incorporating knowledge-sharing mechanisms. In terms of practice, the study guides organizations to strengthen cross-functional collaboration, support sustainable knowledge retention, and align IT capabilities with strategic business objectives. The findings further highlight the relevance of KM in addressing ESG-related goals, particularly the social pillar focused on inclusivity, culture, and governance. The paper concludes by outlining avenues for future research, including the need to examine the influence of artificial intelligence, digital architecture, and enterprise modeling on the evolving relationship between KM and BITA.